Promoting Supplementary Materials Based on Pupil’s Book: A Solution from Integrated Textbook Interplayed Content - Sukarman, Surya Aulia; Wirza, Yanty; Setyarini, Sri; Safira, Viera (JALL (Journal of Applied Linguistics and Literacy), 2024)
The prominence of integrated textbooks in English Language Teaching (ELT) has significantly increased, as many textbooks now include not only a primary book (Pupil’s book) but also supplementary materials such as Teacher’s Handbook, Students’ Workbook, Cassette, etc. Despite this, the utilization of the pupil's book along with its additional resources remains relatively low. This raises the question of whether there is still potential for teachers and students to effectively employ the pupil's book without relying on its supplementary materials. Utilizing a case study research design, this study examined key aspects of the textbook that are considered advantageous in the materials development process. The findings indicate that elements such as the aims and approach, content, methodology, exercises, and activities in the pupil's book exhibit strong coherence with its supplementary materials. Notwithstanding this circumstance, educators possess the capacity to formulate both individual and group activities exclusively through the utilization of the pupil's book as a foundational resource, without dependence on supplementary materials.